As Knowers and Narrators: A Case Study of African Girlhood. Issue 1 (1st March 2023) - Omotoso, Sharon Adetutu; Ogbebor, Ejemen
Abstract: Expanded feminist narratives on the girl child have paid little attention to how young girls have become agents of their own change and sharers of their own knowledge. In this study, we spotlight girls' agency reinforced by institutions that transform them from recipient to agents of change and resilience. In this qualitative study, we deploy critical analysis and reflective argumentation to underscore how Women's Research and Documentation Center (WORDOC) of the Institute of African Studies University of Ibadan provided Do-It-Yourself (DIY) tactics to girls aged 10 to 18 between 2018 and 2019 at its annual WORDOC Girls' Summit. We explore a version of African girlhood aimed at presenting institutional impacts that offer platforms for girls' self-empowerment and girl-agency in Nigeria.